2011
DOI: 10.1001/archophthalmol.2010.373
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and Risk of Developing Open-Angle Glaucoma

Abstract: Methods: Participants from the Rotterdam Study, a prospective population-based cohort study, were considered eligible if they participated at both baseline and follow-up and if they had no OAG at baseline. All participants underwent an identical ophthalmologic examination at all visits, including intraocular pressure measurements, optic nerve head assessment, and perimetry. Lifestyle-related factors were assessed by questionnaires by trained research assistants or measured during the examinations (body mass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
90
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 51 publications
6
90
1
2
Order By: Relevance
“…Gasser et al 27 found no correlation between BMI and primary open-angle glaucoma (POAG), and other studies have actually observed less incident POAG in obese women. 28,29 It may, however, be possible that weight loss and lowering of BMI may result in IOP reductions of similar magnitudes. This requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Gasser et al 27 found no correlation between BMI and primary open-angle glaucoma (POAG), and other studies have actually observed less incident POAG in obese women. 28,29 It may, however, be possible that weight loss and lowering of BMI may result in IOP reductions of similar magnitudes. This requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Although the relation between T2D and POAG is not ironclad, 11,12 no population-based study has shown an inverse relation between the two conditions. In contrast, numerous prior reports support inverse associations between the other components of MetSyn (elevated blood pressure [summarized by Caprioli et al 13 ], higher body mass index, 14,15 and dyslipidemia 7 ) and POAG. Interestingly, the inverse relation between body mass index and POAG seems to be specific for women in some studies.…”
mentioning
confidence: 90%
“…Interestingly, the inverse relation between body mass index and POAG seems to be specific for women in some studies. 14,15 Although the reasons why some components of MetSyn are associated with increased IOPV but not with increased risk of POAGVare complex and not completely understood, the consistent associations between insulin resistance and IOP and between T2D and POAG deserve more attention. Certainly, the work of Park et al 2 showing that elevated IOP is related to fasting blood glucose after menopause is intriguing and may provide important clues regarding the pathogenesis of both T2D and POAG.…”
mentioning
confidence: 99%
“…66 The presence of cardiovascular disease and structural vascular wall changes has been variably linked to the presence of GON during recent years, with some studies identifying strong associations in POAG [67][68][69] and NTG 39,70,71 patients individually and others revealing no such associations. [72][73][74][75] The variability in results between these previous studies could in part be accounted for by differences in the inclusion/exclusion of patients with already diagnosed systemic vascular disease, especially because arterial stiffness is a measure of vascular function. 76 Because most patients with glaucoma seen in day-to-day practice experience several vascular pathologies, a careful selection of only patients free from such diseases could bias results toward very rare occurrences.…”
Section: Commentmentioning
confidence: 99%